Review paperThe role of leptin in inflammatory connective tissue diseases - Maciejewska-Stelmach, Joanna; Śliwińska-Stańczyk, Paula; Łącki, Jan K. (Reumatologia/Rheumatology, 2007)
Leptin is a protein hormone produced mainly by adipocytes. The best known function of leptin has been maintained normal body weight. Leptin also takes part in the cytokine cascade. This protein plays the role of a pro- and antiinflammatory cytokine. Currently leptin is being investigated in many fields of medicine including rheumatology. Up till now leptin has been proposed to be used as a nutritional and prognostic marker in connective tissue diseases. Leptin is also thought to increase incidence of rheumatic diseases. Further studies of anti-leptin therapy should be done because leptin takes part in pathogenesis of connective tissue diseases and modulates immune homeostasis.